2011
DOI: 10.4103/0975-1475.85294
|View full text |Cite
|
Sign up to set email alerts
|

An anthropometric analysis of facial height, arch length, and palatal rugae in the Indian and Nepalese population

Abstract: Introduction:A country such as India abounds with diverse population groups with distinct anthropometric characteristics. Among these, numerous Nepalese population groups are present in different states of India comprising one of the most common immigrant races. The aim of the study is to compare two distinct races, Indians and Nepalese on the basis of facial height proportions, arch length and palatal rugae patterns and assess their significance in racial identification.Materials and Methods:A total of 120 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
22
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 12 publications
12
22
3
1
Order By: Relevance
“…This finding indicates the need for describing/identifying other shapes and conducting a larger scale study. The findings of this study confirm previous findings with respect to Egyptian and Saudi children [1], Saudi adults [9], and Indians [13,21,26] where wavy and curved rugae are the most common shapes followed by straight rugae. The results are also consistent with those reported for Australian Aborigines and Caucasian populations as they, too, are found to have a higher prevalence of wavy-and curved-shaped rugae [14].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding indicates the need for describing/identifying other shapes and conducting a larger scale study. The findings of this study confirm previous findings with respect to Egyptian and Saudi children [1], Saudi adults [9], and Indians [13,21,26] where wavy and curved rugae are the most common shapes followed by straight rugae. The results are also consistent with those reported for Australian Aborigines and Caucasian populations as they, too, are found to have a higher prevalence of wavy-and curved-shaped rugae [14].…”
Section: Discussionsupporting
confidence: 82%
“…The results are also consistent with those reported for Australian Aborigines and Caucasian populations as they, too, are found to have a higher prevalence of wavy-and curved-shaped rugae [14]. Departing from this trend, however, wavy-shaped rugae are the most prevalent followed by diverging rugae in Jordanians [19], and wavy followed by straight and curved are the most prevalent among Rwandans [11] and Nepalese [13]. Despite the fact that the wavy shape seems to be the most dominant pattern in most studied populations, the variability in percentages and the order of other shapes present indicates the need for population-specific studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study the average number of primary rugae has been approximately three in number in accordance with human studies done previously [21]. The number of primary rugae was seen to be greatest in Class II div 2 patients, probably due to difference in degree of development of maxillary basal arch width and transverse morphology.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, the mean straight pattern was more among males and mean circular pattern was the least among females. These results are in contrary to the study conducted by Paliwal et al 8 and Kallianpur et al, 9 who said that the predominant shape was wavy. Intergroup comparisons of rugae shape revealed that the curved type was more among males and the wavy type higher in females, which was statistically significant.…”
Section: Discussioncontrasting
confidence: 56%